Tribological properties of nanostructured coatings for roller screw mechanisms. (November 2019) - Morozov, V.; Kochetov, D.; Dovbysh, N.; Zhdanov, A.
Abstract: In this paper, a comparative analysis of two nanostructured PVD-coatings based on chromium is carried out. Tribological and physical-mechanical characteristics of these coatings for friction RSM rollers are determined. Kinematic characteristics of roller screw mechanism with these types of coatings are obtained, ranges of kinematic transfer functions of friction roller screw mechanism with nanostructured PVD-coatings based on chromium are determined.